2012
DOI: 10.1007/s00428-012-1285-0
|View full text |Cite
|
Sign up to set email alerts
|

Gliomatosis peritonei is associated with frequent recurrence, but does not affect overall survival in patients with ovarian immature teratoma

Abstract: Gliomatosis peritonei (GP) is commonly associated with ovarian teratoma and is not thought to have an adverse prognostic effect. However, the prognostic impact and characteristics of GP remain to be clarified. In this study, we investigated the clinicopathologic features of ovarian teratoma associated with GP, and we further compared ovarian immature teratoma (IT) with GP to ovarian IT without GP. During the study period, there were a total of 16 ovarian teratomas associated with GP. Among them, 15 cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
1
42
0
2
Order By: Relevance
“…Long follow-up studies have demonstrated its benign course (Fortt et al, 1969;Robboy et al, 1970). A recent study comparing ovarian immature teratomas with and without GP demonstrated a similar overall good survival but with a higher incidence of early recurrences in the cases associated with GP (Mann et al, 2008;Yoon et al, 2012). Occasionally, GP may precede highly malignant neuroectodermal tumours (Dadmanesh et al, 1997;Shefren et al, 1991;Trabelsi et al, 2002).…”
Section: Clinical Featuresmentioning
confidence: 97%
See 2 more Smart Citations
“…Long follow-up studies have demonstrated its benign course (Fortt et al, 1969;Robboy et al, 1970). A recent study comparing ovarian immature teratomas with and without GP demonstrated a similar overall good survival but with a higher incidence of early recurrences in the cases associated with GP (Mann et al, 2008;Yoon et al, 2012). Occasionally, GP may precede highly malignant neuroectodermal tumours (Dadmanesh et al, 1997;Shefren et al, 1991;Trabelsi et al, 2002).…”
Section: Clinical Featuresmentioning
confidence: 97%
“…Among serum markers, CA125 levels are elevated in GP (Yoon et al, 2012) and some authors (Bahari et al, 1980;de Graaff et al, 1980;Hokama et al, 1991) have also reported elevated alphafetoprotein levels, possibly related to endodermal elements present in the immature teratoma deposits.…”
Section: Clinical Featuresmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study the 2-yr recurrence-free survival rates were 59.3 and 96.3%, respectively, for patients with immature teratoma associated with gliomatosis, and those without gliomatosis. The authors concluded that gliomatosis was an adverse prognostic factor in patients with immature teratoma (28).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to assess for recurrence in the follow-up examination. In addition to IM recurrence, gliomatosis peritonitis (GP) and growing teratoma syndrome (GTS) can develop after treatment for IM (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%